2009
DOI: 10.1152/ajpregu.90945.2008
|View full text |Cite
|
Sign up to set email alerts
|

Augmented uterine artery blood flow and oxygen delivery protect Andeans from altitude-associated reductions in fetal growth

Abstract: The effect of high altitude on reducing birth weight is markedly less in populations of high- (e.g., Andeans) relative to low-altitude origin (e.g., Europeans). Uterine artery (UA) blood flow is greater during pregnancy in Andeans than Europeans at high altitude; however, it is not clear whether such blood flow differences play a causal role in ancestry-associated variations in fetal growth. We tested the hypothesis that greater UA blood flow contributes to the protection of fetal growth afforded by Andean anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
141
2
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 110 publications
(164 citation statements)
references
References 31 publications
9
141
2
12
Order By: Relevance
“…The women were classified as Andean, European, or mestiza on the basis of self-identification, and classification was verified by reference to parental and grandparental surnames and, in the case of the 20 longi-tudinally studied healthy Andeans or Europeans, a panel of 100 ancestry-informative genetic markers (AIMs), as described previously. 16,54 A woman was classified as Andean if she had 3 or more Andean parental surnames and/or at least 76% AIMs of indigenous American origin. European ancestry was assigned if 3 or more parental surnames were of non-Hispanic European origin, she was of European nationality, or the majority of her AIMs were of European or other low-altitude-population origin.…”
Section: Subjectsmentioning
confidence: 99%
“…The women were classified as Andean, European, or mestiza on the basis of self-identification, and classification was verified by reference to parental and grandparental surnames and, in the case of the 20 longi-tudinally studied healthy Andeans or Europeans, a panel of 100 ancestry-informative genetic markers (AIMs), as described previously. 16,54 A woman was classified as Andean if she had 3 or more Andean parental surnames and/or at least 76% AIMs of indigenous American origin. European ancestry was assigned if 3 or more parental surnames were of non-Hispanic European origin, she was of European nationality, or the majority of her AIMs were of European or other low-altitude-population origin.…”
Section: Subjectsmentioning
confidence: 99%
“…Augmenting this longitudinal sample was a cross-sectional cohort of 120 women living in La Paz or El Alto, all but one of whom was Andean. Women were classified as Andean or European by self-identified ancestry as verified from a panel of ancestry-informative gene markers (AIMs) and parental and grandparental surnames as previously described (25). Participant exclusion criteria were maternal smoking, chronic hypertenslon, gestational or other forms of diabetes, absence of birth weight data, or failure for their DNA samples to pass quality control (QC) as described below, leaving a total of 245 participants whose data are reported here (Fig.…”
Section: Study Participantsmentioning
confidence: 99%
“…Each participant provided biographical information (age, altitude of birth, self-identified ancestry, parental and grandparental surnames and ethnicity, body weight before pregnancy, number of previous pregnancies and live births) on a questionnaire that was administered in her native language. Phenotypic studies were conducted in the longitudinal cohorts at both altitudes at pregnancy weeks 20 and 36 and 3-4 mo postpartum for a measurement in the nonpregnant state (25). The cross-sectional cohort was studied once between 17 and 43 wk of pregnancy with an average of 31.1 wk (Ϯ 5.7 SE) (10).…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumtepe et al (8) demonstrated a greater incidence of eclampsia among women living at high altitudes (>1500 m). There are studies in the literature comparing the effect of altitude on maternal and fetal Doppler flow parameters; however, these studies have conflicting results (9)(10)(11)(12)(13)(14)(15). For instance, Galan et al (14) reported no uteroplacental or fetal vascular Doppler velocimetry differences between moderate highlanders and lowlanders, whereas Krampl et al (11) reported a lower impedance of uterine artery blood flow in women living at a high altitude than at the sea level.…”
Section: Introductionmentioning
confidence: 99%